Methodologies and Intelligent Systems for Technology Enhanced Learning 7th International Conference - Vittorini, Pierpaolo; Gennari, Rosella; Di Mascio, Tania; Rodríguez, Sara.; De la Prieta, Fernando; Ramos, Carlos; Azambuja Silveira, Ricardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the outcomes of the 7th International Conference in Methodologies and Intelligent Systems for Technology Enhanced Learning (MIS4TEL'17), hosted by the Polytechnic of Porto, Portugal from 21 to 23 June 2017. Expanding on the topics of the previous conferences, it provided an open forum for discussing intelligent systems for technology enhanced learning (TEL) and their roots in novel learning theories, empirical methodologies for their design or evaluation, stand-alone and web-based solutions, and makerspaces. It also fostered entrepreneurship and business startup ideas, bringing together researchers and developers from industry, education and the academic world to report on the latest scientific research, technical advances and methodologies.
A Fuzzy-based Multi-Agent Model for Group Formation in Collaborative Learning Environments -- Adaptive agent-based environment model to enable the teacher to create an adaptive class -- The Design of a Smart Tray with its Canteen Users: a Formative Study -- Assessing the Role of Computer Simulation in Chemistry Learning -- TEL methodologies in Health Education. Effectiveness of a group educational intervention in patients with T2DM -- First Steps Towards the Design of Tangibles for Graph Algorithmic Thinking.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence